Determinants of low family planning use and high unmet need in Butajira District, South Central Ethiopia - Mekonnen Wubegzier; Worku Alemayehu (BMC, 2011)
Abstract Background The rapid population growth does not match with available resource in Ethiopia. Though household level family planning delivery has been put in place, the impact of such programs in densely populated rural areas was not studied. The study aims at measuring contraception and unmet need and identifying its determinants among married women. Methods A total of 5746 married women are interviewed from October to December 2009 in the Butajira Demographic Surveillance Area. Contraceptive prevalence rate and unmet need with their 95% confidence interval is measured among married women in the Butajira district. The association of background characteristics and family planning use is ascertained using crude and adjusted Odds ratio in logistic regression model. Results Current contraceptive prevalence rate among married women is 25.4% (95% CI: 24.2, 26.5). Unmet need of contraception is 52.4% of which 74.8% was attributed to spacing and the rest for limiting. Reasons for the high unmet need include commodities' insecurity, religion, and complaints related to providers, methods, diet and work load. Contraception is 2.3 (95% CI: 1.7, 3.2) times higher in urbanites compared to rural highlanders. Married women who attained primary and secondary plus level of education have about 1.3 (95% CI: 1.1, 1.6) and 2 (95% CI: 1.4, 2.9) times more risk to contraception; those with no child death are 1.3 (95% CI: 1.1, 1.5) times more likely to use contraceptives compared to counterparts. Besides, the odds of contraception is 1.3 (95% CI: 1.1, 1.6) and 1.5 (1.1, 2.0) times more likely among women whose partners completed primary and secondary plus level of education. Women discussing about contraception with partners were 2.2 (95% CI: 1.8, 2.7) times more likely to use family planning. Nevertheless, contraception was about 2.6 (95% CI: 2.1, 3.2) more likely among married women whose partners supported the use of family planning. Conclusions The local government should focus on increasing educational level. It must also ensure family planning methods security, increase competence of providers, and create awareness on various methods and their side effects to empower women to make an appropriate choice. Emphasis should be given to rural communities.